2019
DOI: 10.1016/j.scitotenv.2018.11.224
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide survey of 31 organophosphate esters in sewage sludge from the United States

Abstract: Organophosphate esters (OPEs) are used as flame retardants and plasticizers in a wide range of consumer products. Nevertheless, studies on the occurrence and inventory of OPEs in sewage sludge are limited. In this study, 20 OP triesters and 11 diesters were measured in 75 archived sewage sludge samples collected from 67 wastewater treatment plants (WWTPs) across the United States (US). The median concentrations of ∑ 20 OP-triesters and ∑ 11 OP-diesters in sludge were 1,290 and 78.4 ng/g dry weight (dw), respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 57 publications
0
39
0
Order By: Relevance
“…2017 ; Li et al. 2019b ; Wang and Kannan 2018 ; Wang et al. 2019 ), either owing to its spontaneous/microorganism production from known APEs ( Fu et al.…”
Section: Introductionmentioning
confidence: 99%
“…2017 ; Li et al. 2019b ; Wang and Kannan 2018 ; Wang et al. 2019 ), either owing to its spontaneous/microorganism production from known APEs ( Fu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Organophosphate (OP) esters (flame retardants, plasticizers) were measured across the U.S. in sludge samples with resulting estimates of mass inputs via land application of 12,400–14,900 kg/year of OP triesters and 663–796 kg/year of OP diesters (Wang, Kannan, Kannan, Halden, & Kannan, 2019). It is also of note hazard assessments conducted for 14 of the OP esters suggested a low level of risk based on current land application practices (Wang et al, 2019).…”
Section: Analysis and Quantification Of Characteristicsmentioning
confidence: 99%
“…This has been extensively reiterated [21,32,33]. To handle the issues related with the gaseous form of hydrogen and the security concerns related with a hydrogen storage tank, it appears to be sensible to produce and utilize hydrogen as hydroxy gas (HHO) through the HHO generation unit [34][35][36]. Several studies concluded that poor burning and lower thermal efficiencies obtained through conventional fuels could be improved when a blend of hydrogen and LPG were utilized as an auxiliary fuel [37,38].…”
Section: Introductionmentioning
confidence: 99%